2011
DOI: 10.1074/jbc.m111.305284
|View full text |Cite
|
Sign up to set email alerts
|

The Transition from Closed to Open Conformation of Treponema pallidum Outer Membrane-associated Lipoprotein TP0453 Involves Membrane Sensing and Integration by Two Amphipathic Helices

Abstract: Background: TP0453 is the only lipoprotein in T. pallidum known to be associated with the outer membrane (OM). Results: TP0453 adopts closed and open conformations; opening is associated with membrane sensing/insertion. Conclusion: Two amphipathic helices are responsible for amphiphilic behavior of the molecule. Significance: TP0453 is a novel bacterial lipoprotein whose amphiphilic behavior may contribute to T. pallidum OM biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 56 publications
0
32
0
1
Order By: Relevance
“…Pore formation assays were performed using large unilamellar vesicles (LUVs) loaded with the fluorophore Tb(DPA) 3 3Ϫ as previously described (40,48). Immunologic reagents.…”
Section: Methodsmentioning
confidence: 99%
“…Pore formation assays were performed using large unilamellar vesicles (LUVs) loaded with the fluorophore Tb(DPA) 3 3Ϫ as previously described (40,48). Immunologic reagents.…”
Section: Methodsmentioning
confidence: 99%
“…After protein purification, the protein was concentrated using Amicon-Ultra centrifugal filters (EMD Millipore, Billerica, MA). Treponema pallidum protein TP0453 and E. coli OmpF were purified as described elsewhere (49,50).…”
Section: Methodsmentioning
confidence: 99%
“…Pore formation assays were performed as described previously (50,62). Liposomes loaded with Tb(DPA) 3 3Ϫ were diluted in 50 mM Tris (pH 7.5), 100 mM NaCl supplemented with 5 mM EDTA to a concentration of 100 M total lipids.…”
Section: ϫmentioning
confidence: 99%
“…The mechanism(s) by which the parasite acquires and utilizes these essential nutrients can potentially help explain the peculiar membrane biology of T. pallidum, elucidate key aspects of its parasitic strategy, and prompt new avenues of investigation for potentially novel antimicrobial drug targets. To this end, we have found that many of the likely transport systems of T. pallidum are predicated on the organism's membrane lipoproteins (5)(6)(7)(8)(9)(10)(11)(12)(13), and, as a result, the organism devotes a large percentage of its genome to encoding these lipoproteins (3,14,15). Unfortunately, many of the putative lipoproteins are hypothetical (i.e.…”
mentioning
confidence: 99%